UNIT 9.7 Nonrandom X Chromosome Inactivation Detection. (21st January 2014) - Jones, Julie R.
Abstract: X chromosome inactivation patterns may be clinically useful in assessing tumor clonality, determining carrier status for certain X‐linked disorders and evaluating the pathogenicity of a genetic variant identified in an X‐linked gene. The protocols in this unit utilize the highly polymorphic trinucleotide repeat within the first exon of the human androgen receptor gene ( AR ) and the methylation‐sensitive restriction enzyme Hpa II to distinguish between the maternal and paternal alleles and simultaneously determine their methylation status. The data obtained from these protocols can be used to calculate the ratio of inactivation between the two alleles that ultimately reflects whether a female has a random or nonrandom pattern of X chromosome inactivation. Curr. Protoc. Hum. Genet . 80:9.7.1‐9.7.7. © 2014 by John Wiley & Sons, Inc.